Application of models of behavior change communication in various stages of healthcare - George, Sylvia; Jha, Anupriya; Giri, Anjan Kumar (International Journal Of Community Medicine And Public Health, 2024)
A resource-limited country like India calls for a deeper focus on preventive health than it is now. So far, behaviour change communication (BCC) has been more or less limited to campaigns and awareness activities. Treating physicians applying BCC interventions in their clinics is particularly rare. This article aims to describe the role of BCC at the primary healthcare level in preventing diseases. The article also attempts to highlight the importance of BCC in helping cure and rehabilitate patients. Evidence-based interventions can be derived from BCC models that help physicians handle their patients better. Health education an already defined domain of health promotion will be the key to achieving the said goal. It promises to be one of the cheap and effective tools in achieving the vision of universal healthcare. It provides room for flexibility and customised care for each patient. After a thorough understanding of various models and theories of BCC, a physician should be able to apply them on a regular basis in their day-to-day interaction with patients in the most scientific manner possible.